Protein p56 from the Bacillus subtilis phage ϕ29 inhibits DNA-binding ability of uracil-DNA glycosylase - Serrano-Heras, Gemma (Oxford University Press, 2007)
Protein p56 (56 amino acids) from the Bacillus subtilis phage ϕ29 inactivates the host uracil-DNA glycosylase (UDG), an enzyme involved in the base excision repair pathway. At present, p56 is the only known example of a UDG inhibitor encoded by a non-uracil containing viral DNA. Using analytical ultracentrifugation methods, we found that protein p56 formed dimers at physiological concentrations. In addition, circular dichroism spectroscopic analyses revealed that protein p56 had a high content of β-strands (around 40%). To understand the mechanism underlying UDG inhibition by p56, we carried out in vitro experiments using the Escherichia coli UDG enzyme. The highly acidic protein p56 was able to compete with DNA for binding to UDG. Moreover, the interaction between p56 and UDG blocked DNA binding by UDG. We also demonstrated that Ugi, a protein that interacts with the DNA-binding domain of UDG, was able to replace protein p56 previously bound to the UDG enzyme. These results suggest that protein p56 could be a novel naturally occurring DNA mimicry.